(untitled) (Arquivos em Odontologia, 2019)
Aim: This study sought to verify the ability of the polishing system to reduce the surface roughness of IPS E.max ceramics after finishing with diamond drills. Methods: Ten specimens were made from lithium disilicate ceramic blocks, crystallized, and glazed (Group G1) before being subjected to reading with a portable rugosimeter at three different points. Occlusal adjustment was simulated with fine-grained cylindrical diamond burs (Group G2) and re-read before performing the polishing sequence with the EVE Diapol H8 Kit (Group G3), consisting of three rubber diamond discs with decreasing granulations. After analyzing the surface roughness of the last group, the means of the three measurements were submitted to ANOVA statistical analysis and to the Tukey test with a significance level of 5%. Results: The analysis of the data revealed a statistically significant difference between the three groups, with the roughness in the G2 Group being greater than that in the G1 Group, which in turn was greater than that in the G3 Group. Conclusion: It was therefore concluded that the EVE Diapol H8 polishing system effectively reduced surface roughness after finishing with diamond drills and provided a surface smoothness that is superior to that given by the glaze.